Effectiveness of electric vehicle incentives in the United States. (August 2018) - Jenn, Alan; Springel, Katalin; Gopal, Anand R.
Abstract: Transportation accounts for 28% of total energy use and 26% of carbon emissions in the US, and battery electric and plug-in hybrid electric vehicles are promising options to decarbonize transportation. Federal and state governments, electric utility operators, and a number of other entities have provided support to accelerate electric vehicle purchases via monetary and non-monetary incentives. In this paper, we evaluate the effect of these incentives on the adoption of electric vehicles. We find that every $1000 offered as a rebate or tax credit increases average sales of electric vehicles by 2.6%. We also find that HOV lane access is a significant contributor to adoption, the effect is a 4.7% increase corresponding to density of HOV lanes (every 100 vehicles per hour). In addition, we introduce a novel variable to capture consumer knowledge of EVs and associated incentives in our model to help explain the state level heterogeneity in response to incentives and find that raising consumer awareness is critical to the success of EV incentive programs. Highlights: $1000 in rebate corresponds to increase of 2.6% in sales. HOV access contributes 4.7% increase per 100 vehicles using lane per hour. Knowledge of incentives is crucial in explaining differences between state efficacy of incentives.